MXene nanofluids in advanced applications: An in-depth review of thermophysical characteristics and technological innovations - Kulandaivel, Sridhar; Ngui, Wai Keng; Mahendran, Samykano; Mohd Fairusham, Ghazali; Reji Kumar, R.; Suraparaju, Subbarama Kousik; Nurhanis Sofiah, Abd Ghafar (Elsevier, 2025)
Nanofluids have emerged as a promising solution to the challenge of enhancing heat transfer in modern energy applications. MXene-based nanofluids stand out due to their exceptional optical and thermophysical properties, making them highly suitable for diverse industrial applications. However, challenges such as agglomeration and stability have hindered their widespread commercial adoption despite their potential. This review provides a comprehensive overview of MXene nanofluids, focusing on their synthesis, properties, and strategies to manage accumulation and stability. The review highlights innovative approaches to mitigate agglomeration issues while enhancing thermal properties and ensuring long-term stability in heating and cooling applications. The transformative potential of MXene nanofluids extends to electronics, automotive cooling systems, renewable energy, and biomedical applications. This review underscores the importance of future research efforts to examine the stability and physical characteristics of MXene nanofluids thoroughly. By laying the groundwork for further exploration, this review serves as a valuable resource for researchers seeking to optimize MXene nanofluids for specific applications, promising improvements in heat transfer efficiency, economic feasibility, and environmental sustainability compared to conventional heat transfer fluids.